The surgical management and treatment of metastatic lesions in the proximal femur: A mini review. Issue 28 (July 2016) - Feng, Helin; Wang, Jin; Xu, Jianfa; Chen, Wei; Zhang, Yingze
Abstract : Abstract: Review current treatments of metastatic lesions in the proximal femur. We reviewed published literature related to diagnosis and surgical treatments and summarized current treatment options. Surgical management mainly consist of internal fixation, hip replacement, and percutaneous femoroplasty (PFP) which has been newly applied in clinical practice. An appropriate series of treatments is necessary for patients to avoid the occurrence of paraplegia and prolong survival time.